The modelling and simulation of quantum nanostructures for single-electron transistors - Mat Isa, Ahmad Radzi; Ahmad Dasuki, Karsono; Kasmin, Mohd. Khalid; Lee, Jia Yen; Musa, Nor Muniroh (Faculty of Science, 2008)
Nanostructures such as quantum dot and nanocluster have occupied the centre of scientific interest because of their unique electronic nature. Among the materials that has attracted the research is silicon. The structure of silicon quantum dot is intended for the development of single-electron transistors (SET). The fundamental aspects in the study are the density of states (DOS) and the bandstructures of the silicon nanoclusters. The calculation of these parameters is carried out by using VASP (Vienna Ab- Initio Software Package) which utilizes the method of density functional theory and plane wave basis set. In order to speed up the computational time, parallelization was implemented on VASP. In the study, silicon clusters with surface passivated by hydrogen, SinHm are simulated to obtain the density of states (DOS) as well as bandstructure for each cluster. The DOS graphs show discrete spectrum instead of bulk-like continuous DOS which is the evolvement from bulk to nano-size. Bandstructure graphs also show the discrete energy level in consistence with the discrete energy spectrum from DOS. The study shows that the bandgap for hydrogenated silicon clusters increases with the decrease in size. Bare silicon clusters, Sin are also simulated from 1 to 15 number of silicon atom (n). The ground state structure is obtained through an optimization procedure. The bandgaps for the ground state silicon clusters do not show a decreasing trend with the increment of cluster size as that of hydrogenated silicon cluster. The electronic structures of optimized clusters are affected by the surface orientation of the clusters. A comparison of the bandgap values for SinHm and Sin was made. Finally, the current-voltage (I-V) characteristic and conductance-voltage spectrum (G-V) of single-electron transistor (SET) were studied with a simple toy model. These transport properties have shown the relativity of the electronic structure and the electron transport, where the conductance gap increases with the energy difference between Fermi level of the gold lead and the nearest molecular energy level of silicon cluster.